EFEKTIFITAS PENGGUNAAN METODE DISCOVERY LEARNING TERHADAP HASIL BELAJAR MENULIS KALIMAT BAHASA JEPANG - Megawati Adinda Rizkiningrum; Wilda Liona Suri; Erliyani Erliyani (Jurnal Penelitian Humaniora, 2020)
This research aimed to examine the effectiveness of the use of discovery learning method in writing Japanese sentences. This research used the quasi-experiment method with pretest and posttest design. The population in this research was the students of class X Tourism major with a total of 24 students. The data of this research were obtained from students learning outcomes before and after being treated using the discovery learning method. After three treatments, the students' average pretest score was 17,166 and the average posttest score was 89,583 so that an average difference of 72,417 was obtained. T-test results obtained t-table with a significance level of 5% at the degree of freedom = 46 was 30.82. Therefore, t-count was greater than t-table which meant that Ha was accepted and H0 was rejected. After calculating the average normalized gain, a value of 0.89 was obtained, which was interpreted as a very effective criterion. The results of the research proved that there was an increase in the students learning outcomes after using the discovery learning method. The use of the discovery learning method in Japanese sentence writing skills proved to be very effective and had a great contribution to improve the students’ learning outcomes.